The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/srep45317
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of bone quality variation in layer chickens revealed by a genome-wide association study

Abstract: Skeletal problems in layer chickens are gaining attention due to animal welfare and economic losses in the egg industry. The genetic improvement of bone traits has been proposed as a potential solution to these issues; however, genetic architecture is not well understood. We conducted a genome-wide association study (GWAS) on bone quality using a sample of 1534 hens genotyped with a 600 K Chicken Genotyping Array. Using a linear mixed model approach, a novel locus close to GSG1L, associated with femur bone min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 46 publications
2
19
0
1
Order By: Relevance
“…Previous studies showed a suggestive association of BW with a single SNP on GGA4 [41, 42]. The SNP detected in our investigation was in the LCORL gene, polymorphisms in which are linked with measures of skeletal frame size and adult height.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies showed a suggestive association of BW with a single SNP on GGA4 [41, 42]. The SNP detected in our investigation was in the LCORL gene, polymorphisms in which are linked with measures of skeletal frame size and adult height.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, the GCTA tool was used to calculate the phenotypic variance explained by each suggestive or significant SNP, which was detected by single-trait GWAS. Notably, the fixed effects including the first five PCA eigenvectors, sex and live weight were embedded as covariates to adjust the population stratification and latent relatedness[42].…”
Section: Methodsmentioning
confidence: 99%
“…Destaca-se que os documentos abordam assuntos variados, por exemplo, recomendações sobre construções e equipamentos para unidades produtoras de ovos que possibilitem a expansão da atividade (Neyeloff et al, 1979). Também há a engenharia genética e sua utilização como ferramenta para solução de problemas ósseos das aves de postura (Guo et al, 2017) e as técnicas e equipamentos para detecção dos ovos férteis e fecundos de galinhas e patas (Valdez et al, 2017;Fasenko, 2007;Lawrence et al, 2006). O crescimento da indústria processadora de ovos motivou estudos acerca da tecnologia de descontaminação de ovos cozidos por UV pulsado, sendo considerada uma técnica eficaz para esterilização superficial de ovos cozidos.…”
Section: Resultados Referentes à Temática Central Abordada Pelos Docuunclassified